PENGARUH KEMAMPUAN KERJA APARATUR PEMERINTAH DAERAH TERHADAP KUALITAS PELAYANAN PUBLIK (STUDI KASUS DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA PEKANBARU TAHUN 2014) - Novigasa, Adrian; Ridwan, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The government administrative services which often occurs in the Population Bureau and Logging Civil Pekanbaru was problems caused one of these ability to work the apparatus and quality of human resources in providing in implementing the administrative public service, So that population writer formulate or this ability to work that is How and the Recording apparatus Population Service Civil Pekanbaru in implementing the administrative in 2014 population? How quality of public services In the Population Bureau and Logging Civil Pekanbaru in implementing the administrative in 2014 population? If there is influence ability to work apparatus to quality of public services and Logging in the Population Bureau Civil Pekanbaru in 2014?Types of research that used in this research is quantitative research. Location in this research is in office Population Service and Pecatatan Pekanbaru, the number of civilian populations in this research 117 people, on the number of samples as respondents in this study authors set as many as 75 people (64%) and techniques for withdrawal samples in this study authors use incidental sampling techniques that respondents that I choose when he was at the location in March -April 2015 . To know the image problems that can be discussed, it is done penganalisaan data. In this case I use analysis of correlation Spearmans' Rho trial Ooal Reserves Spearman.Based on the results of research capacity apparatus and quality of public services in the Population Bureau and Logging Civil Pekanbaru in 2014 it can be said that population administration both in the event. And the analysis SPSS using correlation Ooal Reserves Spearmans' ability Rho apparatus in the knowledge, skills and experience significant effect is very strong to quality of public services.Key words : The influence, ability to work , quality of Public Services, the Administration